Small non-coding RNAs add complexity to the RNA pathogenic mechanisms in trinucleotide repeat expansion diseases - Marti, Eulalia; Estivill, Xavier (Frontiers in Molecular Neuroscience, 2013)
Trinucleotide-repeat expansion diseases (TREDs) are a group of inherited human genetic disorders normally involving late-onset neurological/neurodegenerative affectation. Trinucleotide-repeat expansions occur in coding and non-coding regions of unique genes that typically result in protein and RNA toxic gain of function, respectively. In polyglutamine (polyQ) disorders caused by an expanded CAG repeat in the coding region of specific genes, neuronal dysfunction has been traditionally linked to the long polyQ stretch. However, a number of evidences suggest a detrimental role of the expanded/mutant mRNA, which may contribute to cell function impairment. In this review we describe the mechanisms of RNA-induced toxicity in TREDs with special focus in small-non-coding RNA pathogenic mechanisms and we summarize and comment on translational approaches targeting the expanded trinucleotide-repeat for disease modifying therapies.